Pengaruh Kemudahan Penggunaan, Persepsi Konsumen dan Kepercayaan terhadap Loyalitas Pelanggan pada Aplikasi Gofood di Kota Batam - Fitriadi, Risan; Nainggolan, Nora Pitri (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The rapid advancement of digital technology has significantly influenced consumer behavior, particularly in food purchasing patterns. GoFood, a popular food delivery service application, has become a preferred option for urban communities in Indonesia. However, customer loyalty towards GoFood in Batam City remains unstable, with many users frequently switching to competitors due to varying service experiences. This study aims to examine the influence of ease of use, consumer perception, and trust on customer loyalty toward the GoFood application. Employing a quantitative approach with a descriptive research design, data were collected from 100 active users selected through purposive sampling. The data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The results reveal that ease of use has a significant and positive effect on customer loyalty, while consumer perception and trust do not show significant individual influence. Nevertheless, when considered simultaneously, all three variables collectively have a positive and significant impact on customer loyalty. These findings imply that improving app usability should be prioritized, while also maintaining a positive brand image and building customer trust to enhance overall user experience and long-term loyalty.